WAVELET-BASED ANALYSIS OF CEREBROVASCULAR DYNAMICS IN NEWBORN RATS WITH INTRACRANIAL HEMORRHAGES - ALEXEY N. PAVLOV; ALEXEY I. NAZIMOV; OLGA N. PAVLOVA; VLADISLAV V. LYCHAGOV; VALERY V. TUCHIN; OLGA A. BIBIKOVA; SERGEY S. SINDEEV; OXANA V. SEMYACHKINA-GLUSHKOVSKAYA (Journal of Innovative Optical Health Sciences, 2014)
Intracranial hemorrhage (IH) is a major problem of neonatal intensive care. The incidence of IH is typically asymptomatic and cannot be effectively detected by standard diagnostic methods. The mechanisms underlying IH are unknown but there is evidence that stress-induced disorders in adrenergic regulation of cerebral venous blood flow (CVBF) are among the main reasons. Quantitative and qualitative assessment of CVBF could significantly advance understanding of the nature of IH in newborns. In this work, we analyze variations of CVBF in newborn rats with an experimental model of stress-induced IH and adrenaline injection. Our analysis is based on the Doppler optical coherence tomography (DOCT) and a proposed adaptive wavelet-based approach that provides sensitive markers of abnormal reactions of the sagittal vein to external factors. The obtained results demonstrate that the incidence of IH in newborn rats is accompanied by a suppression of CVBF with the development of venous insufficiency and areactivity to adrenaline. We introduce a numerical measure θ, quantifying reactions of CVBF and show that the values θ < 1.23 estimated in the low-frequency (LF) spectral range corresponding to the sympathicus indicate abnormal reactions associated with the development of IH. We conclude that the revealed areactivity of the cerebral veins to adrenaline represents a possible mechanism responsible for pathological changes in CVBF.